Shared passengers & goods urban transport solutions and public transport operators: Which challenges? The case of Milan through an international comparison - Anna Trentini; Campi Alessio; Boscacci Flavio; Malhene Nicolas (European Regional Science Association (ERSA), 2010)
Nowadays, in a sustainable urban development point of view, cities are looking for instruments and policies to ensure an efficient and effective urban mobility for both passengers and goods. Indeed, optimizing passengers and goods flows in the urban area while reducing the externalities linked to direct mobility's improvements, become more and more stressing. Goods transport, long excluded from the city's problems, seems now attract renewed interest both from the traditional players such as institutional or professionals of road transport, but also from the new players such as operators of public transport. Some operators are wondering whether or not to enter further into this issue: design and manage combined urban transport solutions, which allow a smooth sharing of passengers and goods could be a real opportunity to extend their services. Unfortunately, not much is known concerning how these innovative solutions can be integrated into companies' strategy, and examples of involvement of public transport operators in urban goods transport and urban logistics are still few. The aim of this paper is to explore this issue. At first, the concept of combined passengers/goods urban transport is defined and existing solutions are described, carried out on an international survey. Than, experiences of European operators involved in combined passengers/goods urban transport solutions are analysed. From this framework, the paper discusses the conditions and economic factors that may make such solutions an interesting alternative to traditional urban transport services' production. In a last section, some scenarios will be proposed, based on Milan's urban transport system.
Keywords: 330; sustainable urban mobility; city logistics; shared passengers and goods solutions; public transport; Milan